Chicken Coccidiosis: From the Parasite Lifecycle to Control of the Disease - Mesa-Pineda, Carolina; Navarro-Ruíz, Jeffer L.; López-Osorio, Sara; Chaparro-Gutiérrez, Jenny J.; Gómez-Osorio, Luis M. (Frontiers in Veterinary Science, 2021)
The poultry industry is one of the main providers of protein for the world's population, but it faces great challenges including coccidiosis, one of the diseases with the most impact on productive performance. Coccidiosis is caused by protozoan parasites of the genus Eimeria, which are a group of monoxenous obligate intracellular parasites. Seven species of this genus can affect chickens (Gallus gallus), each with different pathogenic characteristics and targeting a specific intestinal location. Eimeria alters the function of the intestinal tract, generating deficiencies in the absorption of nutrients and lowering productive performance, leading to economic losses. The objective of this manuscript is to review basic concepts of coccidiosis, the different Eimeria species that infect chickens, their life cycle, and the most sustainable and holistic methods available to control the disease.